Stimulus of Time-Management Supervisory Skill on Completion of Research Process for Postgraduate Students In Northern Zone Universities, Tanzania (International Journal of Scientific Research and Management (IJSRM), 2024)
This study examined the extent to which time management skills employed by research supervisors enhance the completion of postgraduate students’ research process in universities, of the Northern Zone, Tanzania. Anchored in Face-to-Face Interactive Dissertation Supervision Theory proposed by Wang and Li in 2011, the study employed a convergent design under the mixed-methods research approach. The target population of 1454 including 6 Directors of postgraduate studies, 14 heads of departments, 175 supervisors, 390 PhD continuing students, 635 masters continuing students, 84 PhD alumni, and 150 masters alumni, to make a total of 214 respondents sampled through probability and non-probability techniques. Questionnaires, interview guides, and document analysis guides used to collect data were validated by three research experts from the Faculty of Education at MWECAU. The Cronbach Alpha method and peer debriefing were employed to determine the reliability of questionnaires and interview guides respectively. Quantitative data were descriptively analysed, while qualitative data were thematically summarized and presented in direct quotations. It was found that time management skills are deployed to a moderate extent by supervisors to stir up postgraduate students’ research process. The study revealed further that students’ delays are often due to supervisors’ feedback taking longer than expected, low levels of supervisor-student cooperation, and supervisors not being reachable and not present during consultation hours. The study concluded that supervisors differ in their approaches to time management practices in stimulating and accelerating postgraduate students’ research process across universities. The study recommended that universities should regularly provide supervisors and postgraduate students with time management training so that the research process can be completed on schedule.